EVALUASI PENERAPAN UNDANG-UNDANG PENGELOLAAN ZAKAT DAN AKUNTANSI ZAKAT (PSAK 109) PADA BAZNAS PROVINSI JATIM - INDRAWATI, RINA (Jurnal Akuntansi AKUNESA, 2016)
Potential zakat in Indonesia in 2011 was very large, about Rp 217 Trillion. However, acceptance of the fact that the potential of only about  Rp 2,73 Trillion. This is caused by the lack of public confidence in the transparency or accountability process as well as the accounting records or zakat management process, infaq and shodaqoh conducted by Zakat Management Organization. This study aims to analyze the ZIS management mechanism based on Law No. 23 Year 2011 and Government Regulation No. 14 Year 2014 and accounting treatment of ZIS (PSAK 109) applied to BAZNAS East Java Province as an evaluation of the management of ZIS. These results indicate that management mechanism BAZNAS ZIS in East Java province has not fully implement Law No. 23 Year 2011 and Government Regulation No. 14 Year 2014. Meanwhile, the application adopted by the East Java Provincial BAZNAS not fully in accordance with PSAK 109.